Seminar Parenting: Peran Ayah dalam Pengasuhan Anak Usia Dini di Desa Tanjunganom, Kecamatan Rowosari, Kabupaten Kendal - Maulana Anwar; Aisa Rurkinantia; M Ilham Cholid; M Risman Fajri; Nur Isna Fitriatur Rofiqoh; Bintang Maura Salsa Bila F; Sindi Mayang Sari; Nafa Fitra Diani; Siti Nur Hanifah (Lembaga Pengembangan Kinerja Dosen, 2024)
The presence of both parents plays a crucial role in the development of early childhood, especially in creating an environment that supports their optimal growth and development. Ideally, fathers and mothers work together in parenting with a balanced division of roles. However, in Indonesia, father involvement is often less than optimal because of the view that the father's main task is to earn a living. This study aims to improve the understanding and knowledge of the community, especially in Tanjunganom Village, about the importance of father involvement in child care. Through seminars and mentoring held by the KKN POSKO 5 UIN Walisongo Semarang team, fathers were given insight into the division of roles, monitoring strategies, and evaluation in child care. The results of this activity showed an increase in knowledge among fathers regarding their role in parenting, as well as their ability to balance time between work and child care. Children who are cared for by actively involved fathers show progress in social, emotional, cognitive, and affective development. In conclusion, father involvement in early childhood care is very important to support children's overall development. Fathers who are active in parenting have a stronger relationship with their children, which ultimately makes children more sensitive to their emotions and environment. Therefore, it is highly recommended for fathers to understand that child care is a shared responsibility between father and mother.